Historical Research on Otaq Culture in Sindh - Deedar Hussain Khatti; Ghulam Rasool; Tarique Hussain Keerio, (Progressive Research Journal of Arts & Humanities (PRJAH), 2023)
This research paper delves deeply into the captivating world of Otaq culture in Sindh, aims to illuminate its enduring significance across historical epochs and in contemporary times. Otaq culture, deeply ingrained in the ethos of Sindh, is a testament to the cherished traditions of hospitality, camaraderie, and culinary excellence. It transcends boundaries of color, race and welcomes all with open arms. The study conducts an extensive investigation and offers a comprehensive historical perspective on Otaq culture. Significantly, it pioneers academic exploration into Darya Khan Otaq (a focal point of researchers' inquiry). Employing a robust historical research methodology relies on a rich reservoir of secondary data, meticulously collected from reputable sources including peer-reviewed journals and newspapers. The innovative dimension of this research lies in its aspiration to uncover previously uncharted facets of Otaq culture. Thus, lays the foundation for further exploration. Furthermore, it catalyzes future research, encourages scholars to explore the diverse facets of Otaq culture and fosters academic exploration. Lastly, the findings of the study provide invaluable insights into the enduring influence of Otaq culture on Sindhi society, offers a historical lens through which its contemporary manifestations can be understood as a journey from past to the present.